The Power of Spotify in Improving Listening Skills: English - Talitha Zafirah; Windi Wulandari; Gumarpi Rahis Pasaribu (Rahis Cendekia Indonesia, 2024)
English is an international language with Listening skills being one of the most important abilities. The emergence of Spotify as the largest music platform with the best features and unlimited access is one of the media recommendations to help improve listening skills. This research uses a qualitative method with the data generated obtained from the answers of students from the English study program who were selected as respondents. The results found, show that the power of spotify with habits in use has a good impact on improving listening skills in English.